Virulence Factors in Candida albicans and Streptococcus mutans Biofilms Mediated by Farnesol - Fernandes, Renan Aparecido; Monteiro, Douglas Roberto; Arias, Laís Salomão [UNESP]; Fernandes, Gabriela Lopes [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Barbosa, Debora Barros [UNESP] (Springer Nature, 2018)
The aim of this study was to evaluate the effect of farnesol on the production of acids and hydrolytic enzymes by biofilms of Streptococcus mutans and Candida albicans. The present study also evaluated the time-kill curve and the effect of farnesol on matrix composition and structure of single-species and dual-species biofilms. Farnesol, at subinhibitory concentrations, showed a significant reduction in S. mutans biofilm acid production, but did not alter C. albicans hydrolytic enzyme production. The number of cultivable cells of both microorganisms was significantly reduced after 8 h of contact with farnesol. Extracellular matrix protein content was reduced for biofilms formed in the presence of farnesol. In addition, confocal laser scanning and scanning electron microscopy displayed structural alterations in all biofilms treated with farnesol, which included reduction in viable cells and extracellular matrix. In conclusion, farnesol showed favorable properties controlling some virulence factors of S. mutans and C. albicans biofilms. These findings should stimulate further studies using this quorum-sensing molecule, combined with other drugs, to prevent or treat biofilm-associated oral diseases.
Keywords: Biofilms; Fungi; Quorum sensing; Streptococci; Virulence